Evaluating the Effectiveness of the Capstone Doctrine in Addressing UN Peacekeeping Challenges - Christensen, Colin W. (Tufts Archival Research Center, 2005)
Submitted in partial fulfillment of the degree of Master of Arts in Law and Diplomacy at the Fletcher School of Law and Diplomacy. Abstract: The United Nations originally developed the concept of peacekeeping and has far more experience with the practice than any other international or multi-lateral body. While it possesses substantial expertise in carrying out peacekeeping missions, it now faces a range of serious challenges to its capacity to continue doing so effectively. These challenges are not new, however, and in its long history with peacekeeping the UN has progressively evolved in its approach to the practice. In January, 2008, the Department of Peacekeeping Operations (DPKO) approved the Capstone Doctrine (Capstone) as a way of helping to bring the lessons-learned of past peacekeeping operations under one conceptual roof (Capstone is officially titled the âUnited Nations Peacekeeping Operations, Principles and Guidelines). In this paper I will examine the challenges faced by contemporary peacekeeping and look at how Capstone attempts to respond to these challenges. I conclude that Capstone addresses most, but not all of these challenges. In doing so, it presents a fundamentally conservative vision of peacekeeping, although it also leaves conceptual room open for some expansive interpretations of particular peacekeeping activities. I find that Capstone's direct impact is fairly limited to educational materials and as a potential reference tool for peacekeeping policymakers.